A Practical Aryliodine(I/III) Catalysis for the Vicinal Diamination of Styrenes. Issue 13 (21st March 2019) - Cots, Eric; Flores, Andrea; Romero, R. Martín; Muñiz, Kilian
Abstract: 2, 6‐Disubstituted iodoarenes bearing amide‐functionalized side arms are reported as new structures in redox‐active iodine(I/III) catalysis. In combination with bis‐sulfonimides as nitrogen sources and 3‐chloroperbenzoic acid ( m CPBA) as benign terminal oxidant they catalyze the vicinal diamination of styrenes. The obtained reactivity and selectivity outperform other iodoarene catalyst candidates. This protocol provides a sustainable alternative to previous related protocols for diamination that are based on stoichiometric iodine(III) reagents. Abstract : Rapid and productive : A new iodoarene catalyst promotes the vicinal diamination of styrenes and related compounds under mild reaction conditions with 3‐chloroperbenzoic acid ( m CPBA) as terminal oxidant. This protocol provides a sustainable alternative to previous related protocols for diamination that are based on stoichiometric iodine(III) reagents.